2019
DOI: 10.1177/1074248419868996
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Affect Time to Switch From Warfarin to a Direct Oral Anticoagulant After Change in the Reimbursement Criteria in Patients With Atrial Fibrillation

Abstract: Background: Anticoagulation therapy is recommended for stroke prevention in high-risk patients with atrial fibrillation (AF). This study aimed to estimate the time to switch from warfarin to a direct oral anticoagulant (DOAC) and identify the factors associated with it. Methods: By using claims data, we studied 7111 warfarin-using patients with nonvalvular AF who were aged ≥65 years. The Kaplan-Meier analysis was performed to estimate the time to switch from warfarin to a DOAC, and Cox proportional hazard regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…The majority of the studies were conducted in the United States (n = 10), 27,34,35,38,45,46,53,59,62,69 Nordic countries (n = 8; five, two and one from Denmark, Sweden and Norway, respectively) 33,44,47,48,50–52,63 and the UK (n = 5), 43,54,60,61,66 whereas three studies were multinational 32,37,56 . Claim databases and medical records were the principal type of data sources in most studies (n = 19) 27,33–36,38,40,42,45,51,53,57–59,64,66–69 . Primary care data, with or without linking to other data sources, were used in five studies; of these, four were conducted in the UK 43,54,60,61 and one in France 39 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The majority of the studies were conducted in the United States (n = 10), 27,34,35,38,45,46,53,59,62,69 Nordic countries (n = 8; five, two and one from Denmark, Sweden and Norway, respectively) 33,44,47,48,50–52,63 and the UK (n = 5), 43,54,60,61,66 whereas three studies were multinational 32,37,56 . Claim databases and medical records were the principal type of data sources in most studies (n = 19) 27,33–36,38,40,42,45,51,53,57–59,64,66–69 . Primary care data, with or without linking to other data sources, were used in five studies; of these, four were conducted in the UK 43,54,60,61 and one in France 39 .…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies reported the switching rate of DOACs as a class, with or without individual drug‐level switching 32,36,41,42,47,48,51–55,61,64–66 . Of the studies that assessed the switching rate, 14 studies were exclusively conducted among DOAC users, 33–35,38,41,47,48,51,53,55,59,61,64,66 five studies were in VKA users 44,46,49,57,62 and 13 studies were among users of both DOACs and VKAs 32,36,39,42,43,45,50,52,54,58,60,63,65 . The remaining four studies were focused on a single DOAC (two for dabigatran, 37,56 and one each for rivaroxaban 40 and apixaban 27 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations